2008
DOI: 10.1063/1.2931000
|View full text |Cite
|
Sign up to set email alerts
|

Conversion efficiencies of electron beam energy to vacuum ultraviolet light for Ne, Ar, Kr, and Xe excited with continuous electron beams

Abstract: Continuous 8–15keV electron beams were used to excite Ne, Ar, Kr, and Xe at pressures ranging from 75to1400hPa. Conversion efficiencies of the energy deposited by the electron beam in the gas to vacuum ultraviolet light emitted from excimers are obtained. At pressures above 500hPa, the efficiencies show constant values of 0.31±0.06 for Ne, 0.33±0.04 for Ar, 0.42±0.05 for Kr, and 0.42±0.05 for Xe. Apparent energy conversion efficiencies for practical devices utilizing this excitation technique are also reported. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…The observed atomic lines are similar to those seen by Kurunczi et al (2001) using high-pressure microhollow discharge in He. Emission of H(Lyα) is also observed in pure He by Fuchs et al (1995) using a low-frequency He discharge lamp and by Morozov et al (2008) in pure Ne. Aside from the intense H(Lyα) emission, Fedenev et al (2004) have observed the nitrogen lines from a radiation source using pure He excited by an electron beam.…”
Section: Methodsmentioning
confidence: 88%
“…The observed atomic lines are similar to those seen by Kurunczi et al (2001) using high-pressure microhollow discharge in He. Emission of H(Lyα) is also observed in pure He by Fuchs et al (1995) using a low-frequency He discharge lamp and by Morozov et al (2008) in pure Ne. Aside from the intense H(Lyα) emission, Fedenev et al (2004) have observed the nitrogen lines from a radiation source using pure He excited by an electron beam.…”
Section: Methodsmentioning
confidence: 88%
“…Fig. 1 Photon emission spectra in gaseous Ar due to ordinary scintillations in the VUV measured in [22], NBrS electroluminescence at 8.3 Td theoretically calculated in [15] and avalanche scintillations in the NIR measured in [17,18]. Also shown are the photon detection efficiency (PDE) of the SiPMs (MPPC 13360-6050PE [23]) at an overvoltage of 5.6 V obtained from [24] and the transmittance of the acrylic plate (1.5 mm thick) in front of the SiPM matrix, used in this study…”
Section: Wavelength (Nm)mentioning
confidence: 99%
“…The singlet and triplet excimer states are responsible respectively for the fast and slow emission components observed in proportional EL. Their time constants are of 4.2 ns and 3.1 μs respectively: [8], NBrS EL at 8.3 Td theoretically calculated in [9] and avalanche scintillations in the near infrared (NIR) measured in [10,11]. Also shown are the photon detection efficiency (PDE) of SiPM (MPPC 13360-6050PE (Hamamatsu)) at overvoltage of 5.6 V and the transmittance of the acrylic plate (1.5 mm thick) [12].…”
Section: Electroluminescence Due To Excimer Emissionmentioning
confidence: 99%